PRAKTIK ADOPSI DALAM HUKUM ISLAM DAN HUKUM POSITIF INDONESIA SERTA IMPLIKASINYA TERHADAP SILSILAH KELUARGA - Evita Putri Heriyanto; Amum Mahbub Ali; aminudin (Ta'dibiya, 2026)
This study examines adoption practices through Islamic law and Indonesian positive law, and analyzes their implications for lineage (nasab). Adoption is viewed as a noble form of care for children, especially by families who have not been blessed with offspring. However, in practice, adoption in Sindanghayu Village, Saketi Subdistrict, Pandeglang Regency is often carried out through cultural and social approaches without comprehensive legal understanding. In several cases, adopted children are attributed to adoptive parents and treated as heirs, although Islamic law distinguishes adoption from biological parentage. This research uses a qualitative case study approach by collecting primary data through interviews and observation, supported by secondary data from legal literature, legislation, and Islamic legal sources. The findings show that Islamic law permits child care through kafalah as long as it does not change lineage and does not automatically create inheritance rights. Indonesian positive law requires adoption to prioritize the best interests of the child and to be carried out through court determination. The study concludes that adoption may be practiced as a form of protection and care, but it must preserve the child's original lineage and comply with applicable legal procedures.